PENGEMBANGAN SISTEM INFORMASI PELATIHAN BERBASIS WEB DI BAPELKES SEMARANG - , EKO BERBUDI WURJAYANTO, Dr. Ir Eko Nugroho, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Bapelkes Semarang as Technical implementation Unit at the Ministry of health is responsible to the Board of development and the empowerment of Health human resources. Bapelkes Semarang has the main task to implement training in the health field for the health workers and the public, as well as the training information service according to the legislation in force. As for problems encountered is management of training data in the form of health human resources (HR) or training activities have not done optimally causing problems in presentation of training services information systems. Objective: Developing training information system of based a web in Bapelkes Semarang that according to need an organization to training information service. Methods: The type of research is action research. The design was chosen because the research aim to explorein depth the user needs to be analyzed, which will be agreed as the draft of training information system. Results: This research resulted prototype information system that present straining data with simple features adapted to the needs of informatif in the organization so that can be used easily by the user. Training information system prototype developed useful in the process of recording, storage and management of training data in Bapelkes Semarang. The trial prototype, users feel benefits in obtain data and information quickly and ease because data storage more organized Conclusion: Development of training information system prototype can overcome the problems in the management of training data. Training information system prototype are considered to conform the needs of the information and training services, and makes the user in terms of recording, storage and presentation of information, which will be very useful for planning, implementation, and evaluation of training activities in Bapelkes Semarang